RANCANG BANGUN PROTOTIPE PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) TURBIN PELTON - Syarif, Aida (KINETIKA, 2017)
Hydro power utilization as the power plant has been becoming one of the potential solutions to be applied in overcoming limited electricity supply for society in rural areas. Its utilization has been already applied by using waterwheel or water turbine using head potential energy (waterfall) or kinetic energy (river flow). The design of the Micro Hydro Power Plant (PLTMH) equipment in the laboratory scale is analyzed by some factors , they are valve opener, debit and number of blades. At the influencing of the water flow rate on the rotameter and the effect of the maximum of the nozzle valve opener is actually obtained the best generator performance 7.35% at Overshot Horizontal flow with full aperture 100% and water flow rate at 4.5 GPM. Meanwhile, the best number of blades using is at 16 blades which is influences turbine rotation and electrical power generated is 573,9 rpm and 14,7 Watt.